THE INFLUENCE OF HOMONYMS ON THE PROCESS OF TRANSTERMINOLOGIZATION IN MODERN KARAKALPAK LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The more homonyms you learn, the more they appear, so this problem is an ongoing process. But the appearance of homonyms in terms is limited. When we examine homonyms in terms, we first distinguish between words whose meanings are numerous, and then check whether these meanings are close to one or far from one another. Then words whose meanings are far away are homonymous terms. Although the question of terms is not sufficiently studied in Karakalpak linguistics, the process of homonyms in terms consists of fragmentary studies. Therefore, in this article we will use terminology dictionaries of Karakalpak and other languages. In this situation, we select homonyms for research using the following formats: common word + term and term + term = homonym term.